Biological Control of Schizophyllum Commune Fr. the Seedborne Pathogen of Oil Palm with Antagonistic Bacteria - Dikin, Antarjo (2004)
Schizophyllum commune Fr. is one of the most important seedborne pathogens of oil palm. This pathogen can be isolated from fermented fruits, germinated seeds, rotten fruits and infected seeds. The fungus produced papery and leathery compact white mycelia on both sides of the agar plates and often produced basidiocarps (diameter less than 2 cm) with gills on culture plates. The mycelia produced clamp connections with some hyphae having spinulose projections. The width of the hyphae was 2 to 4 μ. Spores produced from basidiocarp were hyaline, cylindrical and single-celled. S. commune grew on PDA medium added 50 g/L of NaCl at 30-35oC optimum temperature but the mycelia became dormant at 45oC. The fungus grew on PDA medium at pH 5 to 6 and was resistant to 1% sodium hypochloride.Inoculation of S. commune Fr. on non germinating oil palm seeds by contact was found to cause a significant decrease of seed germination to 64.3%. Mycelia covered the germ pores of seeds and penetrated the germ pore to reach the surface of seed kernel. Inoculation of non germinating seeds produced abnormal seedlings, inhibition of germ tube elongation and brown discoloration of plumule and radicle. Inoculation of germinating seeds resulted in stunted growth of seedlings, decreased root growth and reduction in both fresh and dry weights. Histological study of the infected seeds indicated that the mycelia penetrated the rotted fruit to reach the testa through germ pores. Mycelium was unable to directly penetrate the endocarp. In advanced seed infection, white mycelia colonized the surface of seed kernel. Mycelia infected the surface of the testa without formation of ‘appressorium’ to support absorption to the surface of the kernel nor produced ‘haustorium’ for absorption of nutrient from the host. Eight out of 40 bacterial isolates from rotten fruits and infected seeds were found to inhibit the radial growth of S. commune in the range 42.9–79.8% and spore germination. The 8 antagonistic bacterial isolates were clustered into 5 species by Biolog® Identification System and they were Bacillus thermoglucosidasius, Burkholderia cepacia, Pseudomonas aeruginosa, Serratia marcescens and Serratia sp. B. cepacia and Serratia sp. grew on NA medium containing 4% and 6% salt concentration respectively. Both species were able to grow on Nutrient Agar (NA) medium that were incubated at 40oC. Both species grew on NA medium containing 0.5% and 2% sodium hypochloride respectively. Both B. cepacia and Serratia sp. grew on NA medium with pH range 4-8. Dipped vacuum treatment of antagonistic bacteria at 400 mm Hg vac. for 2 minutes significantly reduced the internal infection of the inoculated non germinating oil palm seeds. B. cepacia and Serratia sp. significantly increased percentage of seed germination. Dipped vacuum treatment was also used to treat inoculated germinating seeds at 150 mm Hg Vac. for 2 minutes. The results showed that B. cepacia reduced seedling infection.